A Case Study On Kenya Airways - Christopher, Ajuga (2008)
Kenya Airways established itself as a formidable force in the East Africa and Sub-Saharan Africa at large. Just founded in 1977 after the collapse of the East African Community, Kenya Airways has undergone various restructuring both in terms of administrative and financial management.